(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
It is undeniable that the activities of any enterprise, any organization are associated with risks. Risk characterizes uncertainty, which in turn is associated with the possibility of unfavorable situations (threats) that interfere with the implementation of the enterprise (organization) strategy. Enterprises for successful work must learn how to manage risks, which implies the implementation of a risk management system. How to reduce or minimize negative consequences, how to protect an enterprise from the likelihood of adverse situations and consequences, that is, how to manage risks, how to form, implement, improve a risk management system - these are the main issues of the enterprise’s anti-risk program. The article discusses the possibilities of introducing a risk management system in modern enterprises, formulates the main conclusions on the application of risk management.